Revision as of 08:36, 18 September 2008 by Anders89 (Talk)

So the input will be x(t) and output will be y(t).

x(t) = cos2t

after using Euler's Formula

$ x(t) = \frac{1}{2} * e^{2jt} + \frac{1}{2} * e^{-2jt} $

$ y(t) = t * x(-t) $

$ y(t) = \frac{t}{2} * (e^{-2jt} + e^{2jt}) $

$ y(t) = \frac{t}{2} * (cos(2t) - jsin(2t) + cos(2t) + jsin(2t)) $

$ y(t) = \frac{t}{2} * (2cos(2t)) $

$ y(t) = t * cos{2t} $

Alumni Liaison

Ph.D. on Applied Mathematics in Aug 2007. Involved on applications of image super-resolution to electron microscopy

Francisco Blanco-Silva